Economic diplomacy as a basis and instrument in achieving the objectives of state's economy - Kalčić Nenad; Gavrilović Milan; Macura Milan (Trendovi u Poslovanju)
Economic diplomacy as such includes targeted activities carried out by representatives of one country with representatives of another country, which in their core aim to increase foreign investments, greater volume of exports or imports, as well as strengthening the positions of domestic companies in other countries. In addition to the aforementioned activities, economic diplomacy also includes activities that a country undertakes by participating in international economic organizations as well as joining them. This discipline represents the future and the direction of diplomacy of every modern state that wants to survive in today's market conditions, which are unstable, changing and a decisive factor for every participant. The main goal, focus and function of economic diplomacy must be the protection of national economic interests in every international relationship, whatever level it may be. In this paper, economic diplomacy as a discipline will be dealt with, a short theoretical review will be given, as well as the author's perspectives and views on the progress of the Republic of Serbia and the countries of the region in this field.